The nonlinear relationship between the ratio of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol and the risk of diabetic kidney disease in patients with type 2 diabetes mellitus - Cai, Dan-Xuan; Huang, Ye-Hong; Lin, Ni-Na; Zhang, Yun-Feng; Huang, Shu-Qin; Han, Yun; Hu, Xin-Yu; Cai, Song-Tao; Tao, Yan-Ling (Frontiers in Medicine, 2025)
BackgroundThe ratio of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol (NHHR) is a novel marker related to atherosclerosis, but its role in diabetic kidney disease (DKD) remains unclear. This study investigated the relationship between NHHR and DKD risk in patients with type 2 diabetes mellitus (T2DM) and evaluated its potential as a marker for early DKD screening.MethodsData from adults with T2DM participating in the National Health and Nutrition Examination Surveys (NHANES) from 1999 to 2018 were analyzed. Demographic information, laboratory tests, and other relevant information were collected. To evaluate the correlation between NHHR levels and DKD risk, weighted multivariable logistic regression and weighted restricted cubic spline (RCS) analyses were employed. Furthermore, threshold effect analysis was employed to further explore the relationship at different NHHR levels, and subgroup analyses validated the results.ResultsThe study enrolled a total of 3,243 participants, comprising 1,258 individuals with DKD (38.79%) and 1,985 individuals without DKD (61.21%). The multivariable logistic regression analysis showed that T2DM patients with higher NHHR levels exhibited a 45% reduction in the risk of developing DKD in comparison to those with lower NHHR levels (Q2 vs. Q1: OR 0.55, 95% CI 0.40–0.76). The weighted RCS analysis revealed a nonlinear correlation between NHHR and the risk of DKD in patients with T2DM (P for nonlinear = 0.003), with the RCS plot exhibiting an L-shaped association. A negative association was observed between NHHR levels and the risk of DKD when NHHR was ≤2.82 (OR 0.63, 95% CI 0.49–0.83). A statistically significant correlation between NHHR and DKD risk was not observed when NHHR was >2.82. The subgroup analyses indicated that age may have an interaction effect on this association at higher NHHR levels (p for interaction<0.05).ConclusionOur findings revealed a non-linear relationship between the NHHR levels and the risk of DKD in adult T2DM patients in the United States. Managing the NHHR levels in the right range in T2DM patients can help reduce the risk of DKD. This suggests that NHHR may be a valuable and easily measurable biomarker for identifying those at risk for DKD, thereby promoting early intervention and improved disease management.